Decompensation of cardiorespiratory function and emergence of anemia during pregnancy in a case of mitochondrial myopathy, lactic acidosis, and sideroblastic anemia 2 with compound heterozygous YARS2 pathogenic variants. Issue 7 (8th April 2022) - Rudaks, Laura I.; Watson, Eloise; Oboudiyat, Carly; Kumar, Kishore R.; Sullivan, Patricia; Cowley, Mark J.; Davis, Ryan L.; Sue, Carolyn M.
Abstract: Myopathy, lactic acidosis, and sideroblastic anemia 2 (MLASA2) is an autosomal recessive mitochondrial disorder caused by pathogenic variants in YARS2. YARS2 variants confer heterogeneous phenotypes ranging from the full MLASA syndrome to a clinically unaffected state. Symptom onset is most common in the first decade of life but can occur in adulthood and has been reported following intercurrent illness. Early death can result from respiratory muscle weakness and cardiomyopathy. We report a case of MLASA2 with compound heterozygous YARS2 pathogenic variants; a known pathogenic nonsense variant [NM_001040436.3:c.98C>A (p.Ser33Ter)] and a likely pathogenic missense variant not previously associated with disease [NM_001040436.3:c.948G>T (p.Arg316Ser)]. The proband initially presented with a relatively mild phenotype of myopathy and lactic acidosis. During pregnancy, anemia emerged as an additional feature and in the postpartum period she experienced severe decompensation of cardiorespiratory function. This is the first reported case of pregnancy‐related complications in a patient with YARS2‐ related mitochondrial disease. This case highlights the need for caution and careful counseling when considering pregnancy in mitochondrial disease, due to the risk of disease exacerbation and pregnancy complications.